Evaluation of Indole production and Tellurite reduction for speciation of Candida species and Trichosporon species - -, Afreen; S, Bhattacharyya; A, Sarfraz; A, Sengupta; D, Kumar; R, Kumar; A, Kumar; S, Singh (Eastern Journal of Medical Sciences, 2016)
Background: Candidiasis is one of the commonest infections in man, along with Trichosporon infection. Conventional methods for identification are often delayed, which leads to delay in empirical therapy in these infections. Methods: We here describe two newer methods, i.e. Indole production and Tellurite reduction for identification of these two genera. Results: Both these tests, combined together, were equally good as compared to conventional identification techniques. Conclusion: Indole production and Tellurite reduction are useful tests to identify these common yeast pathogens in the laboratory.